2011
DOI: 10.1002/yea.1900
|View full text |Cite
|
Sign up to set email alerts
|

Substrate analysis of the Pneumocystis carinii protein kinases PcCbk1 and PcSte20 using yeast proteome microarrays provides a novel method for Pneumocystis signalling biology

Abstract: Pneumocystis carinii (Pc) undergoes morphological transitions between cysts and trophic forms. We have previously described two Pc serine/threonine kinases, termed PcCbk1 and PcSte20, with PcSte20 belonging to a family of kinases involved in yeast mating, while PcCbk1 being a member of a group of protein kinases involved in regulation of cell cycle, shape, and proliferation. As Pc remains genetically intractable, knowledge on specific substrates phosphorylated by these kinases remains limited. Utilizing the ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2012
2012
2012
2012

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 69 publications
(67 reference statements)
0
1
0
Order By: Relevance
“…Of note, all of these studies have been conducted using P. cariniiderived genes, mostly due to the information supplied by the genome project. Recent studies have also shown the utility of using yeast proteome microarrays for identification of substrates for kinases of P. carinii (40).…”
Section: Pneumocystis Jiroveciimentioning
confidence: 99%
“…Of note, all of these studies have been conducted using P. cariniiderived genes, mostly due to the information supplied by the genome project. Recent studies have also shown the utility of using yeast proteome microarrays for identification of substrates for kinases of P. carinii (40).…”
Section: Pneumocystis Jiroveciimentioning
confidence: 99%